The Impact Of The Fine Arts Curriculum On Academic Motivation, Self-Efficacy, And Self-Regulation Within A Gender Context Among Fine Arts Students In Saudi Arabian Universities - S. Alrasheed, Hanan Abdulrahman (Universiti Sains Malaysia, 2023)
This study mainly aims to investigate the impact of the existing fine arts curriculum on academic motivation, academic self-efficacy, and academic self-regulation among fine arts students in Saudi universities. The study aims to examine the impact of the moderating role of differences in gender on the relationship between the fine arts curriculum and academic self-efficacy and self-regulation among undergraduate fine arts students in Saudi universities.